Development of strategy to improve the recuperation of regenerative braking energy from electric train - CHONG, KAH YUN (2022)
Electrified rails with the recuperation of regenerative braking energy offer higher energy efficiency, lower carbon footprint, and lower operation costs than other systems without the recuperation of regenerative braking energy. However, unfavorable conditions such as inefficient recovery processes or system overload may arise due to improper energy handling. When these conditions occur, the regenerative braking energy needs to be dissipated via resistor banks to ensure system stability. This study investigates the amount of regenerative braking energy recovered under train operating conditions such as different station distances, train speeds, track elevations, and train’s weight under different loading conditions. The recuperation rate of regenerative braking energy under different conditions is identified to prevent wastage of energy or overload. The rail power supply and distribution systems for Malaysia’s MRT Line 2 are modeled using ETAP - eTraX software. The dynamic behavior of the trains has been included in the simulation model to improve the study’s accuracy. The operating conditions with the highest amount of regenerative braking energy have been identified in this study. The simulation results show that by maintaining the ideal scenario of an optimum station distance of 0.9 km, the maximum efficiency of the regenerative braking system can be up to 60.10%. Maintaining the highest operation speed limits of 100 km/h, lowest elevation, and highest possible weight of the train, which is 253 tons with maximum passengers on board, the efficiency of recuperation of energy can be up to 51.70% for the regenerative braking system. An actual-world measurement is also being studied, and the outcome of the practical results are identical to the simulation outcome.